Folklore, people and place international perspectives on tourism and tradition in storied places - Hunter, Jack; Ironside, Rachael (Routledge advances in tourism and anthropology, 2023)
"Folklore, People and Place is a contribution towards better understanding the complex interconnectivity of folklore, people and place, across a range of different cultural and geographical contexts. The book showcases a range of international case studies from different cultural and ecological contexts showing how folklore can and does mediate human relationships with people and place. Folklore has traditionally been connected to place, telling tales of the land and the real and imaginary beings that inhabit storied places. These storytelling traditions and practices have endured in a contemporary world yet the role and value of folklore to people and places has changed. The book explores a broad range of international perspectives and considers how the relationship between folklore, people and place has evolved for tourists and indigenous communities. It will showcase a range of international case studies from different cultural and ecological contexts showing how folklore can and does mediate human relationships with people and place. By exploring folklore in the context of tourism, this book engages in a critical discussion of the opportunities and challenges of using storied places in destination development. The case studies in the book provide an international perspective on the contemporary value of folklore to people and places engendering reflection on the role of folklore in sustainable tourism strategies. This book will be of interest to students, academics, researchers in fields such as anthropology, folklore, tourism, religious studies, human geography and related disciplines. It will also be of interest to scholars and practitioners of traditional ecological knowledge"--